AKTIVITAS ANTIBAKTERI DAUN KENTUT DAN EKSTRAK BUAH BELIMBING TERHADAP ESCHERICHIA COLI DAN STAPHYLOCOCCUS AUREUS - Melati Yulia Kusumastuti; Samran Samran; Debi Meilani (LPPM Universitas Abdurrab, 2022)
Bacteria is one of the factors that cause infection. These infections can be treat with antibacterial compounds. Plants are one of the greatest sources of antibacterial compounds. Leaves of skunk vine (Paederia foetida L.) and sweet star fruit (Avverhoa carambola L.) are plant parts that commonly used traditionally as wound healing, anti-inflammatory, anti-diarrhea, etc. The purposes of this study were to determine the antibacterial activity of the ethanol extract of skunk vine leaves and sweet starfruit leaves and to determine minimum inhibitory concentration (MIC) against E. coli and S. aureus. Leaves of skunk vine and sweet star fruit were extracted with 96% ethanol. The ethanol extract of each plant was screened for their phytochemicals compound and tested for antibacterial activity. The antibacterial activity test was carried out by using the agar disc diffusion method. The results of the study showed that 500 mg/ml of ethanolic extract of skunk vine leaves and sweet star fruit leaves could inhibited the growth of E. coli bacteria around 28.29 mm and 21.50 mm. Meanwhile, both extracts in the same concentration showed inhibition zones against S. aureus around 24.45 mm and 22.53 mm. It showed that ethanol extract of skunk vine leaves has better antibacterial activities than ethanol extract of start fruit leaves. The MIC of skunk vine leaves extract on both bacteria was 200 mg/ml, while the MIC of sweet starfruit leaves ethanol extract for E. coli was 12.5 mg/ml and S. aureus was 25 mg/ml. This indicates that both ethanol extracts have antibacterial activity against E. coli and S. aureus bacteria.